2021
DOI: 10.3390/vaccines9121404
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations after Receiving COVID-19 Vaccine: A Systematic Review

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has had profound and lasting consequences since 2019. Although vaccines against COVID-19 have been developed and approved under emergency use authorization, various adverse events have also been reported after COVID-19 vaccination. This review was undertaken to help clinicians recognize the possible manifestations and systemic pathogenesis, especially those related to the eye, after receiving COVID-19 vaccination. A systemic search was performed on 22 August 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…The immunological response to the spike antigen or to components of the chimpanzee or human adenovirus can cause ocular diseases [ 4 ]. Recently, several systemic reviews of the COVID-19 vaccine have demonstrated multiple ocular manifestations following vaccination with the ChAdOx1 vaccine, which included corneal graft rejection, acute macular neuroretinopathy (AMN), multifocal choroiditis, acute retinal necrosis, and optic neuritis with longitudinal extensive transverse myelitis [ 4 , 15 ]. Superior ophthalmic vein thrombosis and cerebral venous sinus thrombosis were also reported following the ChAdOx1 vaccine, which may be also related to the mechanism of VITT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunological response to the spike antigen or to components of the chimpanzee or human adenovirus can cause ocular diseases [ 4 ]. Recently, several systemic reviews of the COVID-19 vaccine have demonstrated multiple ocular manifestations following vaccination with the ChAdOx1 vaccine, which included corneal graft rejection, acute macular neuroretinopathy (AMN), multifocal choroiditis, acute retinal necrosis, and optic neuritis with longitudinal extensive transverse myelitis [ 4 , 15 ]. Superior ophthalmic vein thrombosis and cerebral venous sinus thrombosis were also reported following the ChAdOx1 vaccine, which may be also related to the mechanism of VITT.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 7.85 billion doses of COVID-19 vaccines have been administered globally and have resulted in one of the largest-scale vaccination campaigns in modern history [ 3 ]. Ocular adverse events, including abnormalities in anterior and posterior segments, also present in some cases after COVID-19 vaccination, and retinal disease is one of the most common adverse events [ 4 ]. With the unprecedented scale of vaccination for COVID-19 development, the number of rare adverse events is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…The Pfizer-BioNTech mRNA vaccine uses a lipid nanoparticle–encapsulated mRNA that encodes a stabilized prefusion form of the SARS-CoV-2 glycoprotein trimer 9,10 . The vaccine produces high levels of neutralizing antibodies that target the spike proteins in the virus 9,11 . The advantage of an mRNA vaccine is that it is noninfectious, does not integrate into the host genome, and does not induce vector-specific responses 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of an mRNA vaccine is that it is noninfectious, does not integrate into the host genome, and does not induce vector-specific responses 10 . However, it may result in potential ocular inflammatory events due to aberrant activation of the innate and acquired immune systems due to similarities between the SARS-CoV-2 spike glycoprotein and human proteins 11 13 . Stimulation of a strong T-cell response by the vaccine can thus induce autoimmune manifestations because of a close resemblance between vaccine peptide fragments and uveal self-peptides.…”
Section: Discussionmentioning
confidence: 99%
“…These effects vary depending on the eyelid, ocular surface, retina, choroid, and involvement of the optic nerve. COVID-19 can affect ocular structures, particularly the retina, even after recovery, possibly through viral invasion or immune-mediated inflammation [3][4][5][6][7][8][9][10][11]. However, owing to the nonspecific presentation, whether ocular findings after COVID-19 vaccination are associated with vaccination or coincidental remains uncertain.…”
Section: Introductionmentioning
confidence: 99%